Design and construction of an automated prototype pilot for bio-diesel's production in Colombia - Pérez, Óscar Ferney; Palacios, Víctor Alejandro; Romero-Pérez, Leonel; Barrera-Lombana, Nelson (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2007)
The purpose is to develop and to deploy some economically competitive technologies for Biodiesel's  production in Colombia, involving the design and construction of a prototype as a technological development. After studying  different material's characteristics, it was selected the austenitic steel ANSI 304. To the monitoring system and for the automatic variables control of (Temperature, time and speed) two microcontrollers PIC 18F452 were implemented, together with a microcontroller PIC 12F629, in configuration a master-two slaves. For the variables visualization a screen LCD PG128128 was used, with interface graph and configurable  menu by applying a matrix  keyboard. The device registers information of temperature and speed using the memory EEPROM reports  of the master microcontroller to visualize them in graphics, with connection to a PC. Finally the prototype  functioning  was evaluated by the production and  the African  Palm’s  bio-diesel quality analysis. The test consisted in  the determination of the content of methyl esters in the samples that cameo ut of the production process, for which a gas chromatograph Varian 3400 was used. The results show conversions up of 86,23 % in average.